Glorious Position of a Mufassir among Moslem Schoolars | علو منزلة المفسر بين سائر العلماء - Ahmad Kusyairi Suhail (Al-Zahra : Journal for Islamic and Arabic Studies, 2010)
Al Mufassir (Interpreter of Quran) has a glorious position among scholars,because they implement the verses that entirely clear (Muhkamat) and believe inverses that not entirely clear (Mutasyabihat). Besides, they took up their stationin saving al-Quran and saving unlimited knowledge of Allah. Those arementioned in the al-Quran and Hadis. There are tree role models of al mufassiras a representative of tree generation: 1. Ibnu Abbas, is a Mufassir from Sahabatgeneration, he was called as al Habir wa al Bahr (an expert and a sea), 2. Mujahid,is a Mufassir from Tabi’in generation, he was called as a “expert of Tafsir”, and3. Ibn Jarir at Thabari, is a Mufassir from era of sciences codification, and wascalled as a “Imam, Mujtahid, al ‘allamah”. The method of the research is thematicmethod, and the writer studied and described about tree profiles of al Mufassir.The writer refers to the classic tafsir books by critical reading method.